The Past as a Benchmark in Defining Turkey's Status Politics - BELDER, FERİT; MEHMETCİK, HAKAN (SAGE PUBLICATIONS INC, 2021)
This article deals with Turkey's status politics since the 2000s, by employing an aspirational constructivist approach that links social psychology with social constructivism in international relations. It focuses on the temporal side of status, stemming from historical identity construction in Turkish foreign policy (TFP) rhetoric and practices under the rule of the Justice and Development Party (JDP) since 2002. Turkey's status politics is motivated by its past legacies rather than by a peer-to-peer comparison. Therefore, different variances and practices of identity politics in TFP offer valuable insights into its status-seeking practices. The article offers five images of the past that define various role sets and status claims for Turkey.
Keywords: Status; Status politics; Turkey; Turkish foreign policy; STATUS-INCONSISTENCY; FOREIGN-POLICY; NEO-OTTOMANISM; DAVUTOGLU; POWER; WAR